2019
DOI: 10.1161/circresaha.118.314010
|View full text |Cite
|
Sign up to set email alerts
|

Atherosclerotic Conditions Promote the Packaging of Functional MicroRNA-92a-3p Into Endothelial Microvesicles

Abstract: Rationale: Microvesicle-incorporated microRNAs (miRs) are biomarkers and effectors of cardiovascular disease. Whether microvesicle-miR expression is regulated in coronary artery disease (CAD) or not is unknown. Objective: Here, we explore the expression of circulating microvesicle-miRs in patients with CAD and investigate the role of microvesicle-miR in endothelial cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
111
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(113 citation statements)
references
References 67 publications
0
111
1
1
Order By: Relevance
“…Atherosclerosis is widely known to be the driving force behind coronary artery disease and high levels of oxidized LDL are a significant risk factor for atherosclerosis development and progression [82]. Recently, it has been demonstrated that oxidized LDL (oxLDL) has the ability to selectively shuttle miRNAs into MVs [83]. Specifically, miR-92a-3p, miR-222-3p, and miR-26a-5p were selectively sorted into MVs through an oxLDL-dependent mechanism.…”
Section: Heart Disease and Atherosclerosismentioning
confidence: 99%
“…Atherosclerosis is widely known to be the driving force behind coronary artery disease and high levels of oxidized LDL are a significant risk factor for atherosclerosis development and progression [82]. Recently, it has been demonstrated that oxidized LDL (oxLDL) has the ability to selectively shuttle miRNAs into MVs [83]. Specifically, miR-92a-3p, miR-222-3p, and miR-26a-5p were selectively sorted into MVs through an oxLDL-dependent mechanism.…”
Section: Heart Disease and Atherosclerosismentioning
confidence: 99%
“…Hypertension and ACS are pathological conditions that damage the endothelium, triggering cell proliferation, vascular remodeling, and other malignant biological behaviors. [41,42] A previous study considered that the expression of Ki-67 was lower in smokers than non-smokers, [43] but the mechanisms underlying this are still unclear. A meta-analysis reported that low Ki-67 is associated with a lower risk of developing diabetes mellitus, [33] but our study did not find an association between Ki-67 and diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…As a kind of paracrine factor, MVs allow the transfer of cytoplasmic components such as proteins, mRNAs and miRNAs from one cell to another [8]. However, circulating MVs vary in their components, which varies with the different parent cell types or different stimuli, thus playing different biological roles in occurrence and development of diseases [9,12].…”
Section: Discussionmentioning
confidence: 99%
“…MVs are submicron membrane vesicles with the size range of 100 ~ 1000 nm in diameter shed from almost all eukaryotic cells during activation or apoptosis [7]. Multiple experiments have shown that MVs derived from various cell types could play intercellular communication role in diagnostic and therapeutic effects of cardiovascular diseases, mainly by delivering proteins, cytokines and gene messages such as mRNAs and microRNAs (miRNAs) to target cells [8]. Among the components of MVs, miRNAs have been shown to play important roles that regulate the pathophysiological consequences of myocardial I/R injury [9], which can be released from various cells by MVs that protect them from degradation and guarantee their stability and circulation through the blood stream [10], suggesting miRNA in MVs could be a potent therapeutic target and tool for protecting myocardium against I/R injury.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation